Chronic coronary syndromes: recommendations for diagnosis and management : The guide for practical classes of 5th year students specialty "Medicine" - Vizir, V. A.; Demidenko, O. V.; Sadomov, A. S.; Prykhodko, I. B.; Візір, Вадим Анатолійович; Деміденко, Олександр Вікторович; Садомов, Антон Сергійович; Приходько, Ігор Борисович (Запорізький державний медико-фармацевтичний університет, 2023)
The guide was developed for students of 5th courses of medical faculties to help learn internal medicine. It contains recommendations for the diagnosis and management of chronic coronary syndromes, in accordance with the work program in the discipline of "Internal Medicine" for Specialties "Medicine" and "Pediatrics".
Хронічний коронарний синдром: рекомендації з діагностики та лікування